Faktor Risiko Kejadian Leptospirosis Di Wilayah Kabupaten Gresik (Tahun 2017-2018) - Hajar Camelia Dewi; Ririh Yudhastuti (Jurnal Keperawatan Muhammadiyah, 2019)
Leptospirosis is a disease derived from animals with Leptospira bacteria as the main cause. Leptospirosis can occur if the host / human is in contact with animals infected with Leptospira bacteria. In 2017-2018, leptospirosis occurs in the community in several sub-districts in Gresik Regency. The purpose of this study was to determine what risk factors related to the incidence of leptospirosis in Gresik Regency. This study uses an observational method with case control study design with 14 respondents and 14 controls. Analysis was performed by chi square statistical test (α = 0.05) and odds ratio (OR) calculation. Factors studied were standing water, ditch conditions, flood history, presence of vegetation, use of APD while doing risky work, washing hands and feet with soap and the habit of closing food. The results showed 54.5% of leptspirosis patients aged 46-55 years, 50% were male, and 66.7% had a risky job. There is a relationship between the presence of stagnant water (p = 0.0001 and OR = 22), ditch conditions (p = 0.053 and OR = 0.205), APD use (p = 0.000), and washing feet and hands with soap (p = 0.000 and OR = 0.031) with the incidence of leptospirosis. There was no relationship between the history of flooding, the presence of vegetation, and the habit of closing food with the incidence of leptospirosis. Rats were caught by placing 28 traps and found 9 trapped rats. It was concluded that the factors associated with the incidence of leptospirosis in Gresik Regency were the presence of stagnant water, ditch conditions, APD use, and washing hands and feet with soap.